Еstimation of indication error of dynamically-adjusted gyroscopes - Киричук, Юрій Володимирович (Eastern-European Journal of Enterprise Technologies, 2012)
Got method and written program, and also the got results of estimation of cross-coupling of DNG, that set on the vibroisolated platform, on each other taking into account the system of vibrodefence